Influence of Sn precursors on Ge1−xSnx growth using metal-organic chemical vapor deposition. (4th December 2018) - Miki, Yusuke; Takeuchi, Wakana; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: We have investigated the metal-organic chemical vapor deposition (MOCVD) of Ge1− x Sn x epitaxial layers using tetrakis-dimetyl-amino-tin (TDMASn), which is expected to be more easily decomposable than other Sn precursors such as tri-butyl-vinyl-tin (TBVSn). We found that the deposition rate of Sn atoms using TDMASn is higher than that using TBVSn at a growth temperature as low as 300 °C. Also, we examined the MOCVD growth of a high-Sn-content Ge1− x Sn x layer with TDMASn at a low temperature below 300 °C, and we found that the Sn content saturated at about 5%. The volume of precipitated Sn grains on the surface increases with the partial pressure of Sn precursor, the reason why the substitutional Sn content in Ge1− x Sn x is limited despite increasing the partial pressure of a Sn precursor would not be because of the deposition-rate limitation of Sn by surface chemical reaction but the precipitation of Sn in this MOCVD condition with TDMASn.